Healthcare-associated Staphylococcus aureus bacteremia in children: Evidence for reverse vancomycin creep and impact of vancomycin trough levels on outcome - McNeil, J Chase (Pediatr Infect Dis J, 2016)
INTRODUCTION: Elevated vancomycin MICs in S. aureus have been associated with worse clinical outcomes in adults. For invasive MRSA infections in adults, the IDSA recommends targeting vancomycin serum trough concentrations between 15–20 μg/ml. We evaluated trends in vancomycin MICs from healthcare-associated S. aureus bacteremia isolates in children in addition to correlating vancomycin serum trough levels with clinical outcomes. METHODS: Patients and isolates were identified from a prospective S. aureus surveillance study at Texas Children's Hospital (TCH). Healthcare-associated S. aureus bacteremia isolates from 2003–2013 were selected. Vancomycin MICs by E-test were determined and medical records were reviewed. Acute kidney injury (AKI) was defined as doubling of the baseline serum creatinine. RESULTS: 341 isolates met inclusion criteria. We observed a reverse vancomycin creep among MRSA isolates in the study period with a decline in the proportion of isolates with vancomycin MIC ≥ 2 μg/ml (from 32.7% to 5.6%, p<0.001). However, the proportion of MSSA isolates with MIC ≥ 2 μg/ml increased (from 2.9% to 9%, p=0.04). Among patients who had vancomycin troughs performed, there was no difference in duration of bacteremia or fever with vancomycin trough >15 μg/ml vs. < 15 μg/ml. A vancomycin trough > 15 μg/ml was, however, an independent risk factor for AKI. CONCLUSIONS: Vancomycin MICs are shifting among healthcare-associated S. aureus bacteremia isolates with significant differences between MRSA and MSSA at TCH. Higher vancomycin troughs did not improve outcomes in pediatric healthcare-associated S. aureus bacteremia but were associated with increased nephrotoxicity. Further studies are needed to better understand optimal management of children with S. aureus bacteremia.